Impact of task-oriented training on hand function and activities of daily living after stroke - Yoo, Chanuk; Park, JuHyung (Journal of Physical Therapy Science, 2015)
[Purpose] We examined the improvement of hand function and activities of daily living in stroke patients after carrying out task-oriented training. [Subjects] Thirty-two patients who had been diagnosed with stroke and underwent rehabilitation therapy participated in the task-oriented training. [Methods] The participants carried out task-oriented training for 30 min per day for 4 weeks. Their hand function and activities of daily living were evaluated before and after the training. [Results] The task-oriented training had a significant impact in terms of improving hand function and activities of daily living. [Conclusion] According to the results of this study, task-oriented training resulted in improved hand function and activities of daily living in stroke patients.